Neutrophil-Lymphocyte Ratio and Procalcitonin as Predictors of the Severity of Acute Pancreatitis - Dessy Iriana; Ani Kartini; Yuyun Widaningsih; Agus Alim Abdullah (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
The Neutrophil-Lymphocyte Ratio (NLR) and procalcitonin are used to indicate systemic inflammation in variousmedical disorders. Both parameters were determined in this study to predict the severity of acute pancreatitis. This studywas a cross-sectional study using a retrospective approach to patients diagnosed with acute pancreatitis by using medicalrecord data from patients at Dr. Wahidin Sudirohusoso Hospital, Makassar, from January 2014 to May 2019. This studycomprised 35 patients hospitalized with acute pancreatitis, with a similar proportion of males and females. This studydiscovered that the mean age in this study was 44.17±12.9 years. The most prevalent cause was Gallstones (77.1%), themost severe degree was mild (54.2%), and the highest outcome was survival (77.1%). The NLR (9.93±11.19, p=0.011)increased in proportion to severity. However, additional analysis based on classification of disease severity revealed thatonly mild-severe NLR was significant (p=0.005). Procalcitonin (8.13±11.25, p=0.001) increased along with the increaseddisease severity, and the subsequent analysis showed that the distribution of severity was similar. The NLR can predict theseverity of acute pancreatitis but is less effective than procalcitonin. This study required a more proportional subjectpopulation and consideration of other factors.